2021
DOI: 10.3389/fphar.2021.707777
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pharmacological Treatment Effects on Long-Time Outcomes in Heart Failure With Preserved Ejection Fraction: A Network Meta-analysis of Randomized Controlled Trials

Abstract: Beneficial effects of therapeutic drugs are controversial for heart failure with preserved ejection fraction (HFpEF). This meta-analysis aimed to evaluate and compare the interactive effects of different therapeutic drugs and placebo in patients with HFpEF. A comprehensive search was conducted using PubMed, Google Scholar, and Cochrane Central Register to identify related articles published before March 2021. The primary outcome was all-cause mortality. Secondary outcomes were cardiovascular mortality, heart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
10
2
1
Order By: Relevance
“…A previous network meta-analysis demonstrated that, for patients with HF and an LVEF of 40% or more, ARNIs and ACE inhibitors were associated with a significant decrease in the risk of hospital admission for HF, but MRAs were not. 14 These results are partly inconsistent with the results of our analysis. In the previous analysis, a positive result of an ACE inhibitor trial during the first year, rather than a negative result during the entire follow-up, was extracted, 15 and a result of cardiac hospitalization in an MRA trial was extracted as a result of HF hospitalization.…”
Section: Discussioncontrasting
confidence: 82%
“…A previous network meta-analysis demonstrated that, for patients with HF and an LVEF of 40% or more, ARNIs and ACE inhibitors were associated with a significant decrease in the risk of hospital admission for HF, but MRAs were not. 14 These results are partly inconsistent with the results of our analysis. In the previous analysis, a positive result of an ACE inhibitor trial during the first year, rather than a negative result during the entire follow-up, was extracted, 15 and a result of cardiac hospitalization in an MRA trial was extracted as a result of HF hospitalization.…”
Section: Discussioncontrasting
confidence: 82%
“…In a meta-analysis (Khan et al, 2017) higher doses of ACEi or ARB significantly though modestly improved the composite end point of all-cause mortality or HF associated hospitalizations. This finding is supported by recent metaanalysis comparing the impact of ACEi, ARB, beta-blockers and the sGC stimulator vericiguat on all-cause mortality and HF associated need for hospitalization in HFpEF patients (Lin et al, 2021). The meta-analysis included 14 randomized trials.…”
Section: Therapeutic Options In Hfpef Between Facts and Beliefmentioning
confidence: 67%
“…Hence, medications focused on this pathway will not improve mortality as RAAS activity is lower in HFpEF. Instead, the pathophysiology of HFpEF is primarily driven by tissue congestion brought on by elevated heart-filling pressures [ 29 ].…”
Section: Reviewmentioning
confidence: 99%